Model Pembelajaran Self Organized Learning Environment (SOLE) Terhadap Berpikir Kritis Peserta Didik Kelas V Sekolah Dasar - Yanti, Yuli; Siswanto, Elisa; Amriyah, Chairul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to investigate the effect of implementing the Self-Organized Learning Environment (SOLE) learning model on the critical thinking abilities of class V students at SD Negeri 1 Harapan Jaya, Bandar Lampung. This learning model is known as an innovative approach that encourages independent, collaborative learning and scientific discovery The research method used was quasi-experimental with a posttest control group research design. This research sample consisted of two classes, namely the control class which received conventional learning and the experimental class which received learning using the Self Organized Learning Environment (SOLE) model. Data was collected through previously validated critical thinking test instruments. The research results showed that there was a significant increase in the critical thinking abilities of students who received learning through the Self Organized Learning Environment (SOLE) model compared to the control class. These findings indicate that the application of the Self Organized Learning Environment (SOLE) Model is able to encourage the development of critical thinking skills in students at the elementary school level. Apart from that, the results of this research also provide an implication of this research regarding the importance of implementing innovative learning models such as SOLE in improving students' critical thinking skills at the elementary school level. Educators can integrate this model into the curriculum to provide more meaningful and in-depth learning experiences, which can help students develop their critical thinking skills from an early age.